The signal eaudiobook - Carlson, Ron (Recorded Books Inc., 2009)
Well known for his short stories, critically acclaimed author Ron Carlson has been featured in the New Yorker, Harper's Magazine, Esquire, and Best American Short Stories. Carlson has also won a National Endowment for the Arts Fellowship in Fiction, a National Society of Arts and Letters Literature Award, and the 1993 Ploughshares Cohen Prize. Here he captivates audiences with a compelling novel no listener will soon forget.